Targeting the proteasome in advanced renal cell carcinoma: complexity and limitations of patient-individualized preclinical drug discovery - Li, Jielin; Pohl, Laura; Schüler, Julia; Korzeniewski, Nina; Reimold, Philipp; Kaczorowski, Adam; Hou, Weibin; Zschäbitz, Stefanie; Nientiedt, Cathleen; Jäger, Dirk; Hohenfellner, Markus; Duensing, Anette; et al. (Biomedicines, 2021)
Background: Systemic treatment options for metastatic renal cell carcinoma (RCC) have significantly expanded in recent years. However, patients refractory to tyrosine kinase and immune checkpoint inhibitors still have limited treatment options and patient-individualized approaches are largely missing. Patients and Methods: In vitro drug screening of tumor-derived short-term cultures obtained from seven patients with clear cell RCC was performed. For one patient, a patient-derived xenograft (PDX) mouse model was established for in vivo validation experiments. Drug effects were further investigated in established RCC cell lines. Results: The proteasome inhibitor carfilzomib was among the top hits identified in three of four patients in which an in vitro drug screening could be performed successfully. Carfilzomib also showed significant acute and long-term cytotoxicity in established RCC cell lines. The in vivo antitumoral activity of carfilzomib was confirmed in a same-patient PDX model. The cytotoxicity of carfilzomib was found to correlate with the level of accumulation of ubiquitinated proteins. Conclusions: In this proof-of-concept study, we show that patient-individualized in vitro drug screening and preclinical validation is feasible. However, the fact that carfilzomib failed to deliver a clinical benefit in RCC patients in a recent phase II trial unrelated to the present study underscores the complexities and limitations of this strategy.
Gesehen am 13.08.2021